PENGARUH PENERAPAN MODEL PEMBELAJARAN GUIDED NOTE TAKING (GNT) PADA MATERI TERMOKIMIA TERHADAP HASIL BELAJAR SISWA KELAS XI IPA SMA NEGERI 2 PASANGKAYU - Rustam, Rizka; Supriadi, Supriadi; Jura, Minarni Rama (Universitas Tadulako, 2013)
Students in the learning required to take an active role in the learning process . But in fact, there are still many conventional learning that found. This can have an impact on student learning outcomes. Therefore we need an appropriate learning modes and appropriate. One of the learning model that allows students to play an active role in learning is a model guided note taking. This study aims to determine the effect of application of learning models guided note taking on learning outcomes of students of class XI Science SMAN 2 Pasangkau school year 2013/2014. The research sample that is class XI IPA 2 as the class experiment with the number of students 25 people and XI IPA 1 as a control class with the number of students was 27 people. The data was collected using achievement test instruments. Testing research data using t-test statistical analysis of the parties to the prerequisite test was a test for normality and homogeneity tests. Average score of student learning outcomes using the guided note taking learning model was 66.14 while the average score of student learning outcomes that follow the conventional learning 52.5. Based on the analysis of statistical hypothesis t-test with the values obtained by the tcounted = 3.693 and ttable = 1.67. So, tcounted> ttable showing that Ho refused and H1 accepted. It can be concluded that the guided note taking learning model gives higher learning outcomes than conventional learning models.